Translation Procedures Of The Book "Quidditch Dari Masa Ke Masa" : a descriptive study - Ayubadra, Estri (2015)
Jurnal ini meneliti prosedur penerjemahan Newmark (1988) yang digunakan dalam buku "Quidditch Dari Masa Ke Masa" yang diterjemahkan oleh Rosi L. Simamora. Studi menunjukkan adanya sepuluh jenis prosedur penerjemahan yang digunakan. Yang paling sering digunakan adalah shift, diikuti oleh transference, compensation, reduction, expansion, paraphrase, literal, gloss, cultural equivalent, dan yang paling jarang digunakan, naturalisation This paper investigated Newmark's (1988) translation procedures used in book of "Quidditch Dari Masa Ke Masa" translated by Rosi L. Simamora. The study shown that there were ten types of translation procedures used. The most frequently used was shift, followed by transference, compensation, reduction, expansion, paraphrase, literal, gloss, cultural equivalent, and the least frequently used, naturalisation.